Non-linear effects of green finance on air quality in China: New evidence from a panel threshold model - Xiang, Weimin; Qi, Qiao; Gan, Lei (Frontiers in Ecology and Evolution, 2023)
Green finance contributes to economic growth and environmental protection, especially by improving air quality, but the precise effects of green finance development on air quality are poorly understood. This study used data from 30 Chinese provinces from 2014–2020, while considering industrial structure optimization and energy structure as threshold variables to propose a panel threshold model, which elucidates a nonlinear relationship between green finance and air quality in China. The panel data are sorted based on urbanization level, resource dependence, and geospatial distribution to examine the heterogeneous effects of green finance on air pollution. The analysis demonstrated that green finance considerably improves the overall air quality in Chinese provinces, but the effect is gradually weakened with the optimization of industrial structure and the improvement of clean energy efficiency. Moreover, green finance exerts a greater inhibitory impact on air pollution through industrial structure optimization compared to the impact of energy structure optimization. Regional variations in the environmental benefits of green finance were discerned. Resource dependence exacerbates the inhibiting impact of green finance on air pollution in the resource-based regions, while urbanization weakens the environmental benefits of green finance in urbanized regions. In terms of geographical distribution, green finance exhibited the best effect on air quality in western China. These findings shed the light on the positive role of green finance on air quality in China, thereby highlighting its importance for the air quality improvement programs of the provincial scales in China.